The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0104-9224/si2301.04
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Aluminium Alloy Type on Defects Formation in Friction Stir Lap Welding of Thin Sheets

Abstract: Abstract:The weldability in Friction Stir Lap Welding (FSLW) of heat and non-heat treatable aluminium alloys, the AA6082-T6 and the AA5754-H22 aluminium alloys, respectively, are compared. For both alloys, welds were produced in very thin sheets, using the same welding parameters and procedures, and strong differences in welds morphology were found. The strength of the welds was evaluated by performing tensile-shear tests under monotonic and cyclic loading conditions. As-welded and heat-treated samples of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…During the μ-FSW process, heat energy is mainly lost to the BP due to the thermal conduction of the BP, which is called heat loss [9]. The Al-Mg-Si series (AA6xxx) and Al-Mg series (AA5xxx) aluminum alloys are used in many fields [10]. The AA6xxx alloys are widely used in various industries due to their excellent workability, corrosion resistance, and low cost.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the μ-FSW process, heat energy is mainly lost to the BP due to the thermal conduction of the BP, which is called heat loss [9]. The Al-Mg-Si series (AA6xxx) and Al-Mg series (AA5xxx) aluminum alloys are used in many fields [10]. The AA6xxx alloys are widely used in various industries due to their excellent workability, corrosion resistance, and low cost.…”
Section: Methodsmentioning
confidence: 99%
“…The Al-Mg-Si series (AA6xxx) and Al-Mg series (AA5xxx) aluminum alloys are used in many fields [10]. The AA6xxx alloys are widely used in various industries due to their excellent workability, corrosion resistance, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the text, each tool will be identified according to the pin design (CN and CL for the conical and cylindrical pin geometry, respectively) and the pin tip diameter. The welding parameters, which are displayed in Table 2, were defined based on the work conducted by Costa et al [19]. In the next section, the similar welds (S) will be labelled as S6, and the dissimilar welds (D) will be identified according to the base materials positioned in the lap joint.…”
Section: Methodsmentioning
confidence: 99%
“…Any slight variation of the discussed input parameters causes the formation of intermetallic compounds and an external and internal defects like flash formation, groovy edge formation and tunnel defects. Costa et al (2018) compared the weldability of heat treatable AA-6082 T6 aluminium alloy and nonheat treatable AA-5754 H22 aluminium alloy. It is observed that as compare to non-heat treatable aluminium alloy, heat treatable aluminium alloy are more prone to defects formation.…”
Section: Schematic Mechanism Of Materials Flow In Friction Stirmentioning
confidence: 99%